Knowledge, Attitude and Practice on Diabetic Wound Care Management among Healthcare Professionals and Impact from A Short Course Training in Sabah, Borneo - Melvin Ebin Bondi; Syed Sharizman Syed Abdul Rahim; Richard Avoi; Firdaus Hayati; Fatimah Ahmedy; Azizan Omar; Mohammad Saffree Jeffree; Awang Setia Musleh (Logos Medical Publishing, 2020)
Objective: Healthcare professionals with an advanced level of knowledge and skills on diabetic wound care management are needed to effectively manage complex wounds. This study aimed to determine the effects of an educational intervention to enhance the management of wound care among healthcare professionals. Method: This study was part of a quasi-experimental pre-post research design where 82 healthcare professionals were recruited and assigned to intervention and control groups. The participants in the intervention group attended two days of educational intervention training on diabetic wound care management, while there was no intervention in the control group. A questionnaire on knowledge, attitude, and practice was applied before and one-month post-intervention to both groups. Results: Pre-test resulted in a low level of knowledge 72.1% and 74.4%, negative level of attitude 67.4% and 66.7%, and a moderate level of practice 79.1% and 76.9% in both intervention and control groups respectively. Post-test resulted in increasing levels of knowledge (76.7%), positive attitude (100%), and practice (76.7%) in the intervention group. At the same time, there was no significant change in the control group. Repeated Measure ANOVA for within-subject and betweensubject effects resulted in a statistically significant p-value of 0.001 for knowledge, attitude, and practice after the educational intervention. Conclusion: Health professionals have only a moderate level of knowledge on diabetic wound care management. It is important to improve this level by specific trainings and by using a good training module.